Stranding Records of Rorquals (Cetacea: Balaenopteridae) along the East Coast of South Sumatran Waters, Indonesia - Diah Komala Sari; Dewi Rosanti; Ina Aprillia; Ines Chatrina; Gusti Ayu Widayanti; Anis Aryani; Nur Arifah; Muhammad Iqbal (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2026)
This paper documents two rorqual whale stranding events along the eastern coast of South Sumatra, Indonesia, a region where marine mammal records remain scarce. The first event, recorded on 15 January 2021 in Sungai Kong, was identified as a Fin Whale Balaenoptera physalus based on morphological characteristics such as body size and asymmetrical jaw coloration. The individual was successfully refloated and returned to deeper waters. The second event, on 26 February 2026 in Sungai Somor, involved a Bryde’s whale Balaenoptera edeni, identified by the presence of three rostral ridges and characteristic body morphology; despite rescue efforts, the individual later died. Both strandings occurred in shallow, estuarine environments characterized by muddy substrates, mangroves, and strong tidal influences, conditions that may increase stranding risk for large whales. These records provide important baseline data on the occurrence of rorquals in South Sumatran waters and highlight the ecological significance of the region.